Generative AI in Multicultural Classrooms: A Narrative Inquiry into International Students' Experiences - Panmei, Benjamin (International Journal of Multicultural Education, 2025)
This study investigates generative artificial intelligence (GAI) use among international undergraduates in multicultural educational settings at a Thai university. Using narrative inquiry with 64 students from 10 countries, it explores students' discourses and practices around GAI. A deductive thematic analysis revealed key themes: Benefits in learning and efficiency, dependency risks, the need for balance between tool and crutch, and concerns about academic integrity. Students’ uses of GAI included research, information gathering, writing assistance, brainstorming, and language translation, offering nuanced insights into GAI’s role in multicultural higher education.